Moderating Effect of Competitive Dynamics on Social Media Marketing and the Performance of Star Rate Hotels in Kenya - Lukose , Tonny; Lagat , Charles (African Journal of Education,Science and Technology (AJEST), 2022)
The purpose of this study was to investigate the moderated effect of competitive dynamics on the link between social media marketing and firm performance among star rated hotels in Kenya. The specific objectives of the study were to determine the effect of social media marketing and the moderating role of competitive dynamics on the performance of star rated hotels in Kenya. This study employed the use of social media integration theory, dynamic capability theory and social exchange theory to test the relationship between the variables. Explanatory research design was adopted and the targeted population was the 215 star rated hotels listed on the Tourism Regulatory Authority. Each individual hotel produced a single respondent who was the employee in charge of social media marketing activities. Closed ended questionnaires were administered for the respondents to choose their best current situation. Census survey was adopted for the study and all the 215 hotels were studied. Regression analysis was used to analyze the relationship between the variables. Factor analysis was done using principal components analysis. Regression results indicated that social media marketing significantly affects performance positively (p= 0.015<0.05). Competitive dynamics on the other hand did not show significant influence on firm performance but can act as a moderator (p=0.340˃0.05). Moderating role of competitive dynamics was positive and significant (p=0.009˂0.05). The studied evidently showed that the use of social media as marketing tool has positive significant effect on the firm performance of star rated in terms of customer satisfaction, market share growth and realized profits. The findings recommend that hotels adopt the use of SMM for performance enhancement and product innovation. This study contributes to knowledge by looking at the implementation and use of SMM by star rated in Kenya. The results are of great importance to the hotel industry as they can be able to access wide global client reach due to advancement in social technological interactions.